Quantity and quality of sleep in young players of a professional football club. Issue 4 (2nd October 2022) - Merayo, Ana; Gallego, Jose Miguel; sans, Oscar; Capdevila, Lluis; Iranzo, Alex; Sugimoto, Dai; Rodas, Gil
ABSTRACT: Purpose: To investigate the quantity and quality of sleep hours in young athletes in a professional football club, to study if there is a significant relationship with mood state and subjective well-being, and to identify the relationship between sleep and quarterly academic performance. We also explored the relationship between sleep and quarterly academic performance. Method: the study included 261 players of the various age group categories from football at Barcelona Football Club (average age:13.04 ± 3.16). Participants maintained a sleep diary and completed questionnaires on their mood state and the quantity and quality of their sleep. Results: 70% of the athletes slept less hours than recommended by the American National Sleep Foundation. Athletes with worse quantity and quality of sleep showed negative effects on academic results. Conclusions: The results show that the majority of young players sleep less than recommended and show that those who sleep more hours obtain better academic results.